Comorbidity and Association of Posttraumatic Stress, Depression, Anxiety, and Somatic Complaints in COVID-19 Georgian Patients at the Beginning of Pandemic - Sikharulidze, Giorgi; Ratiani, Levan; Sordia, Mariam; Sikharulidze, Elene; Khutsishvili, Tinatin; Lejava, Khatuna; Vermetten, Eric (Current Psychiatry Research and Reviews, 2022)
Background: The global pandemic which the world has been facing for the past two years has demonstrated the need to study the effects of this virus on mental health. Various studies showed that COVID-19 could be a threat to people's mental health and physical health, yet the findings are still very limited. The purpose of the study was to fill an existing gap in the corresponding literature by analyzing Post Traumatic Stress Disorder (PTSD) symptoms, somatic complaints, depression, and anxiety in COVID-19 patients and studying their comorbidity to determine the impact of the virus on the patients’ mental well-being. Methods: Patients diagnosed with COVID-19 took part in the study one month after their discharge from the hospital, accounting for 10% of all COVID-19 patients across Georgia during the research. PTSD Checklist (PCL-5) was used. Depression, somatic symptoms, and anxiety were assessed using the Patient Health Questionnaire (PHQ). Results: The results have shown that COVID-19, as a traumatic event, presents an association with PTSD, depression, anxiety, and somatic complaints. A high prevalence of depression (38,6%), anxiety (34,9%), and somatic symptoms (47%) was displayed. The overall indirect effect of PTSD on somatic symptoms was significant through depression and anxiety: 0.16, 95% CI [0.08, 0.26]. According to the report, the indirect effect of PTSD on somatic symptoms of depression was 0.12, 95% CI [0.05, 0.20]. Conclusion: The study presents important findings on the relations between COVID-19 and patients mental health. Somatic complaints, depression, anxiety, and PTSD symptoms were prevalent in participants even after a month since they had COVID-19. Correlations between somatic complaints, anxiety, depression, and PTSD were also demonstrated. Even though there are various limitations to this study, how COVID-19 could affect mental health warrants further, more detailed research, which is necessary.
Keywords: depression